THE YOUNG AGE OF EARTH - CONSTRAINTS ON ATMOSPHERE AND MANTLE EVOLUTION - Zhang Y. (My University, 1998)
Patterson (1956) established that the age of Earth is close to that of meteorites. Over the last 20 years, workers argued for younger age for core differentiation based on Pb-Pb model ages and tungsten isotopic data and for gas retention based on I-Xe modeling. However, disagreement is abundant, and the young age of Earth has not been widely accepted. In this work, I examine all radiogenic noble gases in the atmosphere and use a model-independent approach and total inversion to show that (1) the Xe-closure age of Earth is 109 +/- 23 million years younger than the formation of meteorite Bjurbole (~4560 Ma) and (2) all radiogenic components of noble gases in the atmosphere can be quantitatively accounted for by production and degassing ~60% of the bulk silicate earth. The agreement between the 129I-129Xe clock and 244Pu-238U-136Xe-134Xe-132Xe-131Xe clock suggests that the volatility of iodine does not affect the 129I-129Xe clock. Earth's Xe-closure age is 4.45 +/- 0.02 Ga, consistent with the model age of Pb and the 146Sm-142Nd, 147Sm-143Nd and 182Hf-182W systematics. On the basis of the consistency of these ages, 4.45 +/- 0.02 Ga probably represents the time when the last Martian-sized planetesimal hit Earth and reinitialized the global clocks.